Right Diaphragmatic Eventration with an Intrathoracic Kidney: Case Report and Review of the Literature - Anibal Carrasco; Ricardo Castro (Case Reports in Surgery)
We aimed to review the publications on the diagnosis of diaphragmatic eventration and report on the clinical presentation and surgical treatment of a female patient aged 17 years. The present case, though quite infrequent, shows the presence of an ectopic thoracic kidney on the right side. The clinical features included dry cough, chest pain, respiratory distress, and bronchial spasms for 4 years; additionally, the patient had episodes of bronchial asthma since her childhood. The right hemithorax presented invasion of the thin loops, right colon, and kidney. The treatment approach was laparoscopic followed by thoracotomy using a dual mesh. The intrathoracic kidney remained in place. The outcome was satisfactory. Diaphragmatic eventration associated with thoracic renal ectopia is a very rare entity, considering the age, sex, and right location of the condition. It represents a clinical and diagnostic challenge; clinicians, radiologists, and surgeons must be alert with a high degree of suspicion in order to correlate symptoms and imaging findings and understand the etiopathogenesis. In addition, they should plan an adequate and individualized surgical repair making use, as far as possible, of the minimally invasive procedures that are currently used.